Iraq Crude Oil Exports – August, September, October 2017 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2019)
Table 1. Iraq Crude Oil Exports – August 2017 Table 2. Iraq Crude Oil Exports – September 2017 Table 3. Iraq Crude Oil Exports – October 2017